Quantitative Structure-Activity Relationship of O-methyl Quercetin Analogs, Structure Modification, and Molecular Docking as Lung Anticancer EGFR-TK Inhibitor - Bina Lohita Sari; Lusi Agus Setiani; Shafana Zahra Aulia (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Cancer arises from the uncontrolled proliferation of cells. Lung cancer stands as one example among the diverse array of cancer types. The main cause of the development of lung cancer is the activation of epidermal growth factor receptor (EGFR)-tyrosine kinases (TK). O-methyl quercetin analogs, as one of the quercetin derivatives, can be potential drug candidates for treating lung cancer. In this study, we disclose our findings that O-methyl quercetin analogs and their modified forms, O-methylamino analogs, predicted EGFR-TK inhibitors as lung anticancer. The O-methylated quercetin analogs can be predicted using a Quantitative Structure-Activity Relationship (QSAR) model. The structures were optimized using the parameterized method 3 (PM3) and analyzed through multiple linear regression (MLR). A lower PRESS QSAR values are used for structural modification of O-methylamino as new compounds. Structures of O-methyl quercetin and O-methylamino analogs were docked to the EGFR-TK receptor using molecular docking. The best QSAR model of IC₅₀ predicted result is expressed as log IC50 = 23.059 + (7.397 × log P) + (0.273 × dipole moment) – (0.005 × heat of formation) – (0.733 × ELUMO) – (0.501 × EHOMO) with statistical parameters: R = 0.966; R2 = 0.933; Fcount/Ftable = 3.829853; and Q2 = 0.752226. The O-methyl quercetin analog QC14 (quercetin 5,3’,4’-trimethyl ether) and the modified derivative QC6_8 (3,5-dihydroxy-2-(3-hydroxy-4-((methylamino)methoxy)phenyl)-7-methoxy-4H-chromen-4-one) exhibited the lowest docking scores. Both compounds interact with the key residue Met769 of the EGFR-TK receptor, suggesting their potential as drugs for lung cancer.